Process, product and technologies for medicinal and aromatic plants - Kumar, Satyanshu (Indian Horticulture, 2023)
This article describes the Standard Operating Protocol (SOP) developments for 22 medicinal and aromatic plants. Also, some of the products and technology developed which could find societal benefits have been discussed here.